Central Control vs. Local Liberties: Environmental Stewardship in Indonesia's Power Struggle - Turnip, Immanuel Harri; Hasibuan, Marhara (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
This paper confronts the contentious power dynamics between central governance and local autonomy in environmental stewardship within Indonesia. It dissects the tug-of-war between centralized control and regional liberties, unveiling the ramifications for environmental management and protection. Through a critical lens, the paper examines how divergent interpretations of authority have precipitated a power struggle with far-reaching implications. It scrutinizes instances where central dominance has stifled local initiatives, constraining innovative approaches to environmental conservation. Conversely, it analyzes scenarios where unchecked regional autonomy has led to environmental exploitation and neglect. Drawing on empirical evidence and case studies, the paper unveils the multifaceted dimensions of this power struggle, encompassing legal ambiguities, political maneuvering, and socio-economic disparities. It highlights the inherent tensions between national environmental imperatives and regional aspirations for self-governance, fueling a discord that undermines sustainable development objectives. Furthermore, the paper interrogates potential pathways forward amidst this power struggle. It advocates for a recalibration of governance structures that reconcile centralized oversight with localized autonomy, fostering cooperative frameworks that empower regions while safeguarding national environmental interests. In conclusion, the paper underscores the urgency of addressing Indonesia's environmental power struggle. It calls for a nuanced approach that navigates the delicate balance between central control and local liberties, forging a path towards collaborative environmental stewardship that transcends political divides and fosters sustainable development for all Indonesians.